2017
DOI: 10.1016/j.bioelechem.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and experimental evaluating bio-electrochemical synthesis — A case study with Clostridium kluyveri

Abstract: Microbial electrosynthesis is a highly promising application of microbial electrochemical technologies for the sustainable production of organic compounds. At the same time a multitude of questions need to be answered and challenges to be met. Central for its further development is using appropriate electroactive microorganisms and their efficient extracellular electron transfer (EET) as well as wiring of the metabolism to EET. Among others, Clostridia are believed to represent electroactive microbes being hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Metabolic networks of the different organisms (Komagataella phaffii formerly Pichia pastoris, Saccharomyces cerevisiae, Escherichia coli, Bacillus subtilis, Corynebacterium glutamicum, Cupriavidus necator formerly Ralstonia eutropha and Clostridium autoethanogenum) were modified from published stoichiometric network analyses (Melzer et al, 2009;Lopar et al, 2013Lopar et al, , 2014Ternon et al, 2014;Unrean, 2014;Kracke et al, 2016;Koch et al, 2017; to fulfill the requirements of this elementary flux mode analysis. Specifically, the networks were integrated with methane assimilation pathways, compiled as follows:…”
Section: Construction Of Metabolic Networkmentioning
confidence: 99%
“…Metabolic networks of the different organisms (Komagataella phaffii formerly Pichia pastoris, Saccharomyces cerevisiae, Escherichia coli, Bacillus subtilis, Corynebacterium glutamicum, Cupriavidus necator formerly Ralstonia eutropha and Clostridium autoethanogenum) were modified from published stoichiometric network analyses (Melzer et al, 2009;Lopar et al, 2013Lopar et al, , 2014Ternon et al, 2014;Unrean, 2014;Kracke et al, 2016;Koch et al, 2017; to fulfill the requirements of this elementary flux mode analysis. Specifically, the networks were integrated with methane assimilation pathways, compiled as follows:…”
Section: Construction Of Metabolic Networkmentioning
confidence: 99%
“…Among them, NR and MV are the most studied ones, especially in fermentations with Clostridia (Du, Jiang, Yu, Tang, & Yang, ; Peguin, Goma, Delorme, & Soucaille, ; Reimann, Biebl, & Deckwer, ). However, in the studies of Choi et al () and Koch et al () with C. tyrobutyricum and C. kluyveri in a cathodic BES no effect of MV was observed, which was attributed to the membrane impermeability of reduced MV (Choi et al, ; Koch et al, ). In contrast, a membrane binding of NR and electron transfer from cathode to C. tyrobutyricum was reported for reduced NR (Choi et al, ), whereas oxidized NR was reported to even inhibit the growth of C. kluyveri (Koch et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…However, in the studies of Choi et al () and Koch et al () with C. tyrobutyricum and C. kluyveri in a cathodic BES no effect of MV was observed, which was attributed to the membrane impermeability of reduced MV (Choi et al, ; Koch et al, ). In contrast, a membrane binding of NR and electron transfer from cathode to C. tyrobutyricum was reported for reduced NR (Choi et al, ), whereas oxidized NR was reported to even inhibit the growth of C. kluyveri (Koch et al, ). With its low RP (−0.525 V vs. Ag/AgCl) NR is suitable to provide electrons to intracellular electron consuming redoxsystems (Harrington et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Using the upgrade kit, two-chamber 1 L electrobioreactors based on batch stirred tank reactors (BSTR) were achieved (see Figure 1 and Figure SI 1). We demonstrated that the material and design of electrodes and other components of the 1 L electrobioreactors can be achieved allowing research on several pure cultures of electroactive microorganisms, e.g., Gluconobacter oxidans (Gimkiewicz et al, 2016), Clostridium kluyveri (Koch et al, 2017), Shewanella oneidensis (Rosa et al, 2017), and genetically modified E. coli (Mayr et al, 2019). However, to what extent the insertion of electrodes, an inlay creating two chambers, and the use of an adapted stirrer as well as removal of chicanes resulted in change of fluid dynamics remained unclear, and is addressed within this study.…”
Section: Introductionmentioning
confidence: 99%